CONCEPTUAL FRAMEWORK OF LEARNING THEORY IMPLEMENTATION IN EDUCATIONAL TECHNOLOGY - Norasykin Mohd. Zaid, contributors; Norah Md. Noor, contributors; Nur Sakinah Mohd. Isa, contributors; Noor Azean Atan, 1977-, contributors; Zaleha Abdullah, editor; Mohd. Nihra Haruzuan Mohamad Said, editor; Masdinah Alauyah Md. Yusof, contributors; Nashasha Nabila Sulaiman, 1991-, contributors; Nur Aminah Rahimsa, 1987-, contributors; Zaidatun Tasir, 1972-, contributors; Nurul Farhana Jumaat, 1986-, contributors; Nurul 'Izzati Hamizan, 1990-, contributors (Johor Bahru, Johor : Penerbit UTM Press, 2018)
Includes bibliographical references and index : p.171-173